Respiratory Muscle Training Improves Diaphragm Citrate Synthase Activity and Hemodynamic Function in Rats with Heart Failure - Jaenisch,Rodrigo Boemo (2017)
Abstract INTRODUCTION: Enhanced respiratory muscle strength in patients with heart failure positively alters the clinical trajectory of heart failure. In an experimental model, respiratory muscle training in rats with heart failure has been shown to improve cardiopulmonary function through mechanisms yet to be entirely elucidated. OBJECTIVE: The present report aimed to evaluate the respiratory muscle training effects in diaphragm citrate synthase activity and hemodynamic function in rats with heart failure. METHODS: Wistar rats were divided into four experimental groups: sedentary sham (Sed-Sham, n=8), trained sham (RMT-Sham, n=8), sedentary heart failure (Sed-HF, n=7) and trained heart failure (RMT-HF, n=7). The animals were submitted to a RMT protocol performed 30 minutes a day, 5 days/week, for 6 weeks. RESULTS: In rats with heart failure, respiratory muscle training decreased pulmonary congestion and right ventricular hypertrophy. Deleterious alterations in left ventricular pressures, as well as left ventricular contractility and relaxation, were assuaged by respiratory muscle training in heart failure rats. Citrate synthase activity, which was significantly reduced in heart failure rats, was preserved by respiratory muscle training. Additionally, a negative correlation was found between citrate synthase and left ventricular end diastolic pressure and positive correlation was found between citrate synthase and left ventricular systolic pressure. CONCLUSION: Respiratory muscle training produces beneficial adaptations in the diaphragmatic musculature, which is linked to improvements in left ventricular hemodynamics and blood pressure in heart failure rats. The RMT-induced improvements in cardiac architecture and the oxidative capacity of the diaphragm may improve the clinical trajectory of patients with heart failure.